2004
DOI: 10.1094/pdis.2004.88.3.312a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Downy Mildew on Basil (Ocimum basilicum) in Italy

Abstract: Sweet basil (Ocimum basilicum) is an economically important herb in several Mediterranean countries. Approximately 80 ha are grown annually in Italy for fresh and processed consumption. In 2003, a damaging foliar disease was observed in several greenhouses located in the Liguria Region of northern Italy. More that 50% of the plants were affected. Leaves of infected plants were initially slightly chlorotic, especially near the central vein. Within 2 to 3 days, a characteristic gray, furry growth was evident on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 0 publications
0
30
0
1
Order By: Relevance
“…Unfortunately these characteristic symptoms can be easily confused with those caused by other foliar pathogens, such as the causal agent of basil downy mildew (Peronospora sp.) (Garibaldi et al, 2004) and basil black spot (Colletotrichum sp.) (Gullino et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately these characteristic symptoms can be easily confused with those caused by other foliar pathogens, such as the causal agent of basil downy mildew (Peronospora sp.) (Garibaldi et al, 2004) and basil black spot (Colletotrichum sp.) (Gullino et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…infections are carefully evaluated, not only on symptomatology, but also on the basis of microscopic observations. Both of the fungal diseases can usually be recognised on the basis of the morphological characteristics of the asexual fruiting bodies (Gullino et al, 1995;Garibaldi et al, 2004), while nematode infection must be determined by dissecting symptomatic material and identifying the emerging nematodes to species level.…”
Section: Discussionmentioning
confidence: 99%
“…Italiano classico (Furia Sementi) of basil, highly susceptible to downy mildew, belonging to the same lot which showed to be naturally contaminated by P. belbahrii in previous trials, were used. The seed lot used in the trials was selected because showed 7-15% of infected basil plants under completely controlled environment conditions in growth chamber at 22°C (12 h day fluorescent light regime), 15-21 days after sowing (Garibaldi et al 2004a). The seed sample was stored at 8°C to maintain seed a stable infection level before starting each trial.…”
Section: Methodsmentioning
confidence: 99%
“…(Hansford, 1933) and later, in the 2000s, reported as responsible of increasingly serious losses in several countries, starting from Switzerland (Lefort et al 2003), Italy (Garibaldi et al 2004a), Belgium (Coosemans, 2004), France (Garibaldi et al 2005), and including USA (Roberts et al 2009), Cuba (Martinez de la Parte et al 2010), and Hungary (Nagy and Horvath, 2011). Nowadays, downy mildew has been observed wherever basil is grown as herb crop as well as for pesto sauce production.…”
Section: Introductionmentioning
confidence: 99%
“…Basil, primarily sweet basil, is used for fragrance, flavour, fresh culinary and dried herb industries (Simon et al 1990(Simon et al , 1999. However, downy mildew caused by Peronospora belbahrii has become destructive for basil production worldwide (Garibaldi et al 2004(Garibaldi et al , 2005; Mart ınez de la Parte et al 2010;McGrath et al 2010;McLeod et al 2006;Nagy and Horv ath 2011;Ronco et al 2008;Voglmayr and Piątek 2008;Wyenandt et al 2015). However, downy mildew caused by Peronospora belbahrii has become destructive for basil production worldwide (Garibaldi et al 2004(Garibaldi et al , 2005; Mart ınez de la Parte et al 2010;McGrath et al 2010;McLeod et al 2006;Nagy and Horv ath 2011;Ronco et al 2008;Voglmayr and Piątek 2008;Wyenandt et al 2015).…”
Section: Introductionmentioning
confidence: 99%